Manipulating heat release features to minimize combustion noise. (1st March 2020) - Denny, Michael; van den Ende, Luc; Persson, Håkan; Andersson, Öivind
Highlights: Triple-pilot diesel injection strategies are compared under varying conditions. Short hydraulic separations are effective at reducing combustion noise. Inlet dilution is also effective at reducing combustion noise. Injection rate shaping is utilized to minimize combustion noise. The ratio of reduced heat release out performs pressure rise rate as a predictor. Abstract: Changes in combustion noise, efficiency, and emissions are investigated as responses to boundary conditions and injection scheduling parameters of closely-coupled multiple-pilot strategies. In order to minimize combustion noise, the heat release rate (HRR) should be as linear in its buildup as possible. Through low injection pressure, high dilution ratio, and close-coupling of the pilot injections, combustion noise can be minimized. It is possible to have too much mixture dilution or dwells which are too short, however. This causes excessive blending of combustion events which tends to increase combustion noise. High injection pressure can significantly decrease soot emissions without significantly increasing combustion noise. This is beneficial since high dilution ratios will increase soot emissions but are desirable to achieve both lower NOx and combustion noise levels. Noise minimization though HRR shaping has also been achieved through injection rate shaping. Based on the learnings from each investigation, triple and quadruple-pilot injection strategies are created for lowest possible combustion noise. The investigations also reveal the relative extent to which emissions, noise, and efficiency are affected by each control parameter so that compromises in each response can be understood.